Inorganic salt modified paper substrates utilized in paper based microfluidic sampling for potentiometric determination of heavy metals - Ding, Ruiyu (2021)
Inorganic salt modified paper substrates were developed and utilized in microfluidic paper based sampling coupled with potentiometric ion sensors for the determination of heavy metals, such as Cd2+ and Pb2+. The application of paper based sampling without any paper substrate pre-treatment were characterized with super Nernstian response, while the paper substrates with inorganic salt pre-treatment were characterized with standard Nernstian response. The application of inorganic salt modified paper substrates was found advantageous when the cation of the salt in the conditioning solution was the same as the primary cations of the ion-selective electrodes (ISEs). A relatively high concentration of inorganic salts during pre-treatment of the paper substrates, namely Cd(NO3)2 or Pb(NO3)2 with subsequent measurement of cadmium(II) and lead(II), by Cd2+- and Pb2+-ISEs, respectively was needed to sustain Nernstian response of sensors. It was also found that paper substrates facilitate sorption of metal ions onto the paper substrates, with stronger binding strength given to Pb2+ over Cd2+. Moreover, the metal-paper interactions suggest concentration dependent sorption-desorption of metal ion, which can have direct limitations of the use of paper based analytics for the determination of low analyte concentration of heavy metals.